Transportation Infrastructures and Arthropod Dispersal: Are Harvestmen (Opiliones) Hitchhiking to Northern Europe?. Issue Volume 38:Issues 1(2018) (March 2018) - Vestbo, Stine; Toft, Søren; Swanson, Heather Anne; Olesen, Jens M.; Funch, Peter
In recent years, as economic globalization and long-distance trade have increased, so has the unintentional transport of non-human species. During the past 30 years, the species diversity of harvestmen (Opiliones) in northern Europe has changed dramatically due to the arrival of new species from southern Europe. Here we explore the changing harvestmen diversity at two scales: 1) the scale of Europe, where we propose the hypothesis that these new, and in some cases invasive, harvestmen species have expanded northwards, aided by the increased traffic along the European transport network, and 2) the scale of specific sites in Central Jutland, Denmark, where we investigated the dispersion of non-native harvestmen species in a former brown coal mining area, as well as areas in the vicinity. We found that the proportion of harvestmen belonging to non-native species was larger in areas characterized by more car and truck traffic than in areas where human disturbance was less frequent. Thus, we theorize that the increase in vehicular transport and intracontinental trade is the main cause of the initially patchy distributions observed for non-native harvestmen in northern Europe. This study provides an example of how succession of non-native species can be driven by specific cultural landscape changes; thus we argue that this type of succession constitutes an important ethnobiological process.